Pendampingan Penyusunan Laporan Keuangan Berdasarkan ISAK No 35 di Yayasan Puri Ratna Juwita - Lusi Tartila; Sri Adella Fitri; Mega Rahmi; Nita Fitria; Rita Masdar (Madani: Jurnal Pengabdian Masyarakat dan Kewirausahaan, 2023)
Puri Ratna Juwita Foundation is a non-profit organization. This foundation is run in the field of education, namely TK and KB Islamic Harapan Ibu. In financial reports, recording is still carried out in a simple manner and also lacks clarity of some transactions and is not yet guided by ISAK 35. The purpose of the researchers in carrying out this PKM activity is to be able to assist the Puri Ratna Juwita Foundation in preparing financial reports that apply and are in line with financial accounting standards ( ISAK 35). The method used in this PKM is with assistance which begins with the initial survey stage, then Focus Group Discussion (FGD), then continues with assistance in preparing financial reports with the foundation until the finalization stage in preparing financial reports. The research results contribute to and increase the understanding of the foundation's management in preparing financial reports based on financial accounting standards from creating account formats to financial reporting.